Acute Cardiometabolic Responses to a Novel Training Rope Protocol in Children. Issue 5 (May 2018) - Faigenbaum, Avery D.; Kang, Jie; Ratamess, Nicholas A.; Farrell, Anne; Golda, Stephanie; Stranieri, Andrew; Coe, Jordan; Bush, Jill A.
Abstract : Abstract: Faigenbaum, AD, Kang, J, Ratamess, NA, Farrell, A, Golda, S, Stranieri, A, Coe, J, and Bush, JA. Acute cardiometabolic responses to a novel training rope protocol in children. J Strength Cond Res 32(5): 1197–1206, 2018—The purpose of this study was to quantify the acute cardiometabolic responses to a novel training rope (TR) protocol in children. Fifteen boys (10.6 ± 1.4 years) were tested for peak oxygen uptake (V[Combining Dot Above]O2 ) on a treadmill and subsequently (2–7 days later) performed a progressive 10-minute protocol of 5 TR exercises (EX): EX1: standing side-to-side waves, EX2: seated alternating waves, EX3: standing alternating waves, EX4: jumping jacks, and EX5: double-arm slams. Participants performed 2 sets of each TR exercise for 30 seconds per set with a 30-second rest interval between sets and exercises. A 12.8-m TR (4.1 kg) was used for all trials, and a metronome was used to standardize cadence. Peak values for V[Combining Dot Above]O2 and HR during the treadmill test were 47.4 ± 8.8 ml·kg −1 ·min −1 and 195.1 ± 6.6 b·min –1, respectively. During the TR protocol, mean V[Combining Dot Above]O2 and HR significantly increased ( p ⩽ 0.05) from set 1 of EX1 (10.3 ± 2.6 ml·kg −1 ·min −1 and 103.2 ± 11.6 b·min –1, respectively) to set 2 of EX5 (30.0 ± 3.9 ml·kg −1 ·min −1 and 168.6 ± 11.8 b·min –1, respectively). Percentage of peak V[Combining Dot Above]O2 and peak HR values attained during the TR protocol ranged from 21.5 to 64.8% and from 52.9 to 86.4%, respectively. These descriptive data indicate that TR exercise can pose a moderate to vigorous cardiometabolic stimulus in children and with proper supervision and instruction may serve as a worthwhile complement to youth fitness programs.